2011
DOI: 10.1021/nn202607r
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Multilayers as Gates for Multi-Week Sequential Release of Proteins from Surfaces

Abstract: The ability to control the timing and order of release of different therapeutic drugs will play a pivotal role in improving patient care and simplifying treatment regimes in the clinic. The controlled sequential release of a broad range of small and macromolecules from thin film coatings offers a simple way to provide complex localized dosing in vivo. Here we show that it is possible to take advantage of the structure of certain nanomaterials to control release regimes from a scale of hours to months. Graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
115
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 45 publications
2
115
0
Order By: Relevance
“…215 Drug delivery systems aim to localize delivery of therapeutic agents, in which GO is predominantly used because it can create barrier layers in multilayer thin films, trapping molecules of interest for controlled release. 216 NGO-PEG has been used as a nanocarrier for delivery of water-insoluble aromatic anticancer drugs into cells. The NGO-PEG loaded with SN38 exhibited high cytotoxicity for HCT-116 cells, 1,000-fold more potent than CPT-11.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…215 Drug delivery systems aim to localize delivery of therapeutic agents, in which GO is predominantly used because it can create barrier layers in multilayer thin films, trapping molecules of interest for controlled release. 216 NGO-PEG has been used as a nanocarrier for delivery of water-insoluble aromatic anticancer drugs into cells. The NGO-PEG loaded with SN38 exhibited high cytotoxicity for HCT-116 cells, 1,000-fold more potent than CPT-11.…”
mentioning
confidence: 99%
“…219 Functionalization of GO with the active targeting ligand TRC105 increased therapeutic efficacy in angiogenesis. 216 A multiple supramolecular assembly was fabricated with a folic acid-modified beta-cyclodextrin, adamantanyl porphyrin, and GO through non-covalent interactions. Owing to the cooperative contribution of these three units, the DOX showed better drug activity and much lower toxicity.…”
mentioning
confidence: 99%
“…29 Prepared GO was exfoliated onto each GO-COO − sheet by ultrasonification in an ice bath. The resultant brown dispersion was centrifuged at 3,470 g for 5 minutes to remove any unexfoliated powder.…”
Section: Preparation Of Gomentioning
confidence: 99%
“…29,34,35 Coating with multiple layers of GO resulted in a full coverage of the Ti substrate ( Figure 1A). Atomic force microscopy revealed that, unlike the bumpy surface of an uncoated Ti substrate, the GOcoated Ti surfaces became much smoother after multiple cycles of LbL deposition.…”
Section: Coating Of Ti Substrates With Gomentioning
confidence: 99%
See 1 more Smart Citation